Intraoperative Confocal Laser Endomicroscopy Ex Vivo Examination of Tissue Microstructure During Fluorescence-Guided Brain Tumor Surgery - Belykh, Evgenii; Zhao, Xiaochun; Ngo, Brandon; Farhadi, Dara S.; Byvaltsev, Vadim A.; Eschbacher, Jennifer M.; Nakaji, Peter; Preul, Mark C. (Frontiers in Oncology, 2020)
Background: Noninvasive intraoperative optical biopsy that provides real-time imaging of histoarchitectural (cell resolution) features of brain tumors, especially at the margin of invasive tumors, would be of great value. To assess clinical-grade confocal laser endomicroscopy (CLE) and to prepare for its use intraoperatively in vivo, we performed an assessment of CLE ex vivo imaging in brain lesions. Methods: Tissue samples from patients who underwent intracranial surgeries with fluorescein sodium (FNa)–based wide-field fluorescence guidance were acquired for immediate intraoperative ex vivo optical biopsies with CLE. Hematoxylin-eosin–stained frozen section analysis of the same specimens served as the gold standard for blinded neuropathology comparison. FNa 2-5 mg/kg was administered upon induction of anesthesia, and FNa 5 mg/kg was injected for CLE contrast improvement. Histologic features were identified, and the diagnostic accuracy of CLE was assessed. Results: Of 77 eligible patients, 47 patients with 122 biopsies were enrolled, including 32 patients with gliomas and 15 patients with other intracranial lesions. The positive predictive value of CLE optical biopsies was 97% for all specimens and 98% for gliomas. The specificity of CLE was 90% for all specimens and 94% for gliomas. The second FNa injection in 7 patients, a mean of 2.6 hours after the first injection, improved image quality and increased the percentage of accurately diagnosed images from 67% to 93%. Diagnostic CLE features of lesional glioma biopsies and normal brain were identified. Seventeen histologic features were identified. Conclusions: Results demonstrated high specificity and positive predictive value of ex vivo intraoperative CLE optical biopsies and justify an in vivo intraoperative trial. This new portable, noninvasive intraoperative imaging technique provides diagnostic features to discriminate lesional tissue with high specificity and is feasible for incorporation into the fluorescence-guided surgery workflow, particularly for patients with invasive brain tumors.